GP81 Early intervention to support preterm infant-parent interaction and development: results of a randomised controlled trial on maternal sensitivity, social-emotional development and parental mental health. (June 2019) - Twohig, Aoife; Segurado, Ricardo; McCarthy, Anthony; Underdown, Angela; Smyke, Anna; McNicholas, Fiona; Molloy, Eleanor
Abstract : Objective: To evaluate the effects of a range of modifying factors on an early attachment focused intervention for parents of very preterm infants in the NICU on maternal sensitivity and infant social-emotional development. Methods: Design and setting: A pragmatic randomised controlled trial in a level III NICU including infants born at 32 weeks gestation and their parents. Exclusion criteria were infant major congenital abnormality and maternal low level of fluency in English. Intervention: comprised reflective interview, observation of infant cues and Video Interaction Guidance (VIG). The primary outcome, maternal sensitivity during playful interaction with her infant was measured by the Child Adult Relationship Evaluation (CARE-Index). Secondary outcomes were infant social-emotional problems measured by the Ages and Stages Questionnaire-Social-Emotional version (ASQ-SE) and self-reported parental mental health. Modification of the effect of the programme on the primary outcome, maternal sensitivity, was explored using general linear model univariate analysis of sociodemographic, maternal and infant characteristics. Significant interactions are presented. Results: Eighty mothers and their preterm infants were randomized to the intervention and standard care groups. The groups were similar in baseline sociodemographic and perinatal characteristics, although more mothers in the intervention group had completed higher-level education and subsequent analyses were adjusted accordingly. At 12 months corrected age (CA) infants in the intervention group had fewer self-regulation problems at 12 months of age (Chi-Square 3.84, df=1, p=0.05, partial eta squared=0.07) and infants whose mothers had received VIG had significantly fewer communication problems (Chi square=20.41, df=6, p=0.002, phi=0.61), however there was no statistically significant difference between the intervention and standard care groups in maternal sensitivity during play at 9 months CA or measures of maternalmentalhealth. Fathers in the intervention group had lower depression scores at folllow up.There was modifying effect of maternal ethnicity (B=4.179, CI=0.921–7.437, p=0.013); there was a significant difference in mean sensitivity of mothers of infants with IVH, (1. 85 points) (CI=0.083–3.614, p=0.041) but there was no significant interaction with group assignment. Conclusion: This early attachment focused intervention integrating VIG for mothers and their very preterm infants had significant positive effects on infant social-emotional problems at 12 months CA.Maternal ethnicity modified the intervention effect